2018
DOI: 10.1002/ajmg.a.40363
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity of patients diagnosed with VACTERL association

Abstract: The combination of vertebral, anal, cardiac, tracheo-esophageal, renal and limb anomalies termed VACTERL association, also referred to as VATER, has been used as a clinical descriptor and more recently, a diagnosis of exclusion, for a specific group of phenotypic manifestations that have been observed to co-occur non-randomly. Though the causes remain elusive and poorly understood in most patients, VACTERL association is thought to be due to defects in early embryogenesis and is likely genetically heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 71 publications
2
9
1
Order By: Relevance
“…In the comparison of the frequencies of component features between our study and three other studies [12,13,17], the percentages of ARM and EA/TEF were similar, most likely because these component features are clearly defined congenital anomalies. This is also reflected in the low percentages of minor VACTERL features for the ARM and EA/TEF components.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In the comparison of the frequencies of component features between our study and three other studies [12,13,17], the percentages of ARM and EA/TEF were similar, most likely because these component features are clearly defined congenital anomalies. This is also reflected in the low percentages of minor VACTERL features for the ARM and EA/TEF components.…”
Section: Discussionsupporting
confidence: 78%
“…GU anomalies were neither considered part of the VACTERL spectrum, nor included in VACTERL-PLUS anomalies when occurring in combination with a renal or anorectal anomaly, as their embryology is partly shared [23]. Several studies reported relatively high frequencies of VACTERL cases with GU anomalies [12,13,23]. Husain et al even proposed to consider another revision of the acronym to include GU anomalies as a component feature of VACTERL [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations